Prana and pranayama - Saraswati, Swami Niranjanananda (Munger Yoga Publications Trust, 2016)
Prana and Pranayama, by Swami Niranjanananda Saraswati, is a comprehensive book on the philosophy of prana the life force, and pranayama the expansion and control of the life force. This book offers a complete explanation of the science of pranayama as presented in the classical texts and as taught in the Satyananda Yoga Tradition by Bihar School of Yoga. The book explores the theory of prana and its related yogic concepts such as koshas, chakras, nadis and mantras. It also discusses respiratory physiology and current research undertaken on pranayama. The book also has a practical section, which contains particular guidelines for practicing pranayama, explained through instructions and illustrations. Throughout the book, biblical sources enhance the reader's understanding, bringing to light the unique spirit and intent of these classical teachings.
Keywords: Hatha yoga; Pranayama